2015
DOI: 10.1371/journal.pntd.0003829
|View full text |Cite
|
Sign up to set email alerts
|

Human-Mediated Marine Dispersal Influences the Population Structure of Aedes aegypti in the Philippine Archipelago

Abstract: BackgroundDengue virus (DENV) is an extraordinary health burden on global scale, but still lacks effective vaccine. The Philippines is endemic for dengue fever, but massive employment of insecticides favored the development of resistance mutations in its major vector, Aedes aegypti. Alternative vector control strategies consist in releasing artificially modified mosquitos in the wild, but knowledge on their dispersal ability is necessary for a successful implementation. Despite being documented that Ae. aegypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…However, it revealed a considerable number of genetic clusters (K=5). These findings are consistent with previous population genetic studies with micro-geographic scales [11,14,16] and local studies in the Philippines [54,59]. Furthermore, these studies reported low genetic differentiation but with substantial number of inferred genetic clusters (K = 3-9).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, it revealed a considerable number of genetic clusters (K=5). These findings are consistent with previous population genetic studies with micro-geographic scales [11,14,16] and local studies in the Philippines [54,59]. Furthermore, these studies reported low genetic differentiation but with substantial number of inferred genetic clusters (K = 3-9).…”
Section: Discussionsupporting
confidence: 92%
“…aegypti by human-mediated transportation. It is believed that mosquito vectors occasionally travel in long distances by taking advantage human-aided transportation routes via land, sea or air [52,53,54] as Ae. aegypti eggs, larvae and adults have been found in commercial trucks and ships through tire importation [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) although fewer have explicitly tested the effects of human transportation on the spread of an invasive species (but see Fonzi et al . regarding boat traffic among islands). Medley et al .…”
Section: Discussionmentioning
confidence: 99%
“…j. japonicus has been human-mediated. Many studies of mosquito population genetics have invoked human-aided long-distance dispersal (LDD) as an explanation for low genetic differentiation between geographically distant populations (Lehmann et al 1996;Huber et al 2004;Brown et al 2011;Brelsfoard & Dobson 2012;Damal et al 2013) although fewer have explicitly tested the effects of human transportation on the spread of an invasive species (but see Fonzi et al 2015 regarding boat traffic among islands). Medley et al (2014) studied the effects of land cover types on the US expansion of another aggressive invader, Aedes albopictus, using nine microsatellite loci.…”
Section: ; Kampen and Werner 2014)mentioning
confidence: 99%